A review on integrated water resource management (IWRM) in Malaysia - Sukereman, Anis Syazwani (2014)
Water resource is getting insecure and turns to conflicting issues if it remains uncontrollable. One of the critical problems that hinder the sustainability of water resource in Malaysia is the water crisis management. In this regard, Malaysia have adopt Integrated Water Resource Management (IWRM) as a holistic approach in order to resolve water crisis management as well as overcome some water issues such as water excesses, water shortage, water pollution, threat from climate change and issues in current state of governance. In view of that, many policies, plans and programmes are being conduct to ensure the IWRM approach can be effectively implement.